“TRAUMA IS SUFFERING THAT REMAINS”. THE CONTRIBUTION OF TRAUMA STUDIES TO PROPHETIC STUDIES - A Groenewald (Acta Theologica)
Although the study of trauma has been common practice in several fields, biblical scholars have, since only a few years ago, used the concept of trauma as an important tool to interpret biblical texts. This article aims to provide a brief overview of the history of trauma studies in order to understand its impact on theology and biblical studies. The last section of the article focuses on trauma studies and the interpretation of prophetic literature.